A new novolimus-eluting bioresorbable scaffold for large coronary arteries: an OCT study of acute mechanical performance. (1st October 2016) - Boeder, Niklas F.; Koepp, Tim; Dörr, Oliver; Bauer, Timm; Mattesini, Alessio; Elsässer, Albrecht; Möllmann, Helge; Blachutzik, Florian; Achenbach, Stephan; Ghanem, Alexander; Hamm, Christian W.; Nef, Holger M.
Abstract: Aims: To evaluate the acute performance of a novolimus-eluting bioresorbable scaffold (BRS) with a nominal diameter of 4.0 mm (DESolve® XL) using optical coherence tomography (OCT) in terms of appropriate scaffold deployment. Methods and results: Ten patients (55.6% male, mean age 60.0 y) undergoing OCT-guided scaffold implantation were enrolled consecutively in this retrospective study. Using data from the final pullback, the following indexes were calculated: mean and minimum area, residual area stenosis, incomplete strut apposition, tissue prolapse, eccentricity and symmetry indexes, strut fracture, and edge dissection. The clinical indication for the procedure was acute coronary syndrome in roughly half (55.5%) of the cases. All three main vessels were affected equally. The maximum post-dilatation balloon inflation pressure was 14.7 ± 4.2 atm. OCT analysis showed a lumen area of 11.4 ± 1.9 mm 2 and a scaffold area of 11.5 ± 2.1 mm 2 . Mean residual area stenosis was 28.6%. No strut fractures or edge dissections were apparent. The mean eccentricity index was 0.65 ± 0.16 and the mean symmetry index 0.39 ± 0.25. Conclusion: The size of large vessels does not adversely influence acute mechanical performance as assessed by the eccentricity and symmetry indexes. No adverse cardiac event occurred during the hospital stay or the 30-day follow-up. It is feasible to treat large vessels with the DESolve® XL BRS.